2005
DOI: 10.1007/s00508-005-321-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow edema syndrome of the femoral head

Abstract: The parenteral application of iloprost can achieve equal or better results in the treatment of bone marrow edema syndrome of the hip compared to core decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…MRI was used to document the regression of the disease during the observation period. In a recent study comparing core decompression with treatment with parenteral iloprost, Aigner36 could show that all patients with bone marrow edema syndrome without demarcation of necrotic areas treated with iloprost yielded the same excellent results with a highly accelerated recovery compared to core decompression. Furthermore, most patients resumed normal daily activities earlier.…”
Section: Discussionmentioning
confidence: 99%
“…MRI was used to document the regression of the disease during the observation period. In a recent study comparing core decompression with treatment with parenteral iloprost, Aigner36 could show that all patients with bone marrow edema syndrome without demarcation of necrotic areas treated with iloprost yielded the same excellent results with a highly accelerated recovery compared to core decompression. Furthermore, most patients resumed normal daily activities earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vasoactive prostacyclin derivatives have been used in bone marrow edema patients to dilate the arterioles and venules. In a study comparing the effects of vasoactive prostacyclin derivatives and decompression, both groups showed a fast clinical recovery, whereas the patients treated with vasoactive prostacyclin derivatives showed a faster healing of the bone marrow edema [ 24 ]. The follow-up course of our patients who had not undergone a biopsy included administration of NSAIDs and restriction of weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aigner et al . 40 compared the results of Iloprost with core decompression in patients with bone marrow edema syndrome. The authors reported the parenteral application of Iloprost resulted in equal or better results compared to core decompression at 3 months comparing the Harris hip score and MRI findings post treatment.…”
Section: Discussionmentioning
confidence: 99%